2012
DOI: 10.1016/j.jalz.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracies of two common screening instruments for classification of Alzheimer's disease, mild cognitive impairment, and healthy aging

Abstract: Objective To compare the utility and diagnostic accuracy of the MoCA and MMSE in the diagnosis of Alzheimer’s disease (AD) and Mild Cognitive Impairment (MCI) in a clinical cohort. Method 321 AD, 126 MCI and 140 older adults with healthy cognition (HC) were evaluated using the the MMSE, MoCA, a standardized neuropsychological battery according to the Consortium to Establish a Registry of Alzheimer’s Disease (CERAD-NB) and an informant based measure of functional impairment, the Dementia Severity Rating Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
323
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(364 citation statements)
references
References 47 publications
19
323
1
5
Order By: Relevance
“…Based on our findings, we may state that the MMSE as well as the MoCA are adequately reliable screening tests. The alpha value found by us (the MMSE α = 0.78 / the MoCA α = 0.81) is lower than the value specified by the MoCA method author (α = 0.83) (Nasreddine et al., 2005); but despite that, these reliability values are sufficient and they are also in accordance with the research findings of the performed psychometric studies (Roalf et al, 2013;Saczynski et al, 2015). Sensitivity and specificity of the MMSE are different in various stages depending on the cut off used.…”
Section: Resultssupporting
confidence: 84%
“…Based on our findings, we may state that the MMSE as well as the MoCA are adequately reliable screening tests. The alpha value found by us (the MMSE α = 0.78 / the MoCA α = 0.81) is lower than the value specified by the MoCA method author (α = 0.83) (Nasreddine et al., 2005); but despite that, these reliability values are sufficient and they are also in accordance with the research findings of the performed psychometric studies (Roalf et al, 2013;Saczynski et al, 2015). Sensitivity and specificity of the MMSE are different in various stages depending on the cut off used.…”
Section: Resultssupporting
confidence: 84%
“…The mean MoCA of 25.86 ± 2.92 in our sample was similar to a smaller sample of individuals with MS [27], 26.02± 2.30 and is in the same range as other neurologic disorders associated with mild cognitive impairment including REM Sleep Behavior Disorder [34] (n=38, 24.34 ± 3.50), or early Parkinson's disease [7] (n=100, 24.9 ±3.1), but is considerably higher than individuals with brain metastasis [36](n=40, 20.53 ± -5.15), cerebral small vessel disease [37] (n=40, 19.2 ± 4.2), Huntington's disease [9](n=53, 21 ±4.4) or Alzheimer's disease [3](n=321,13.0 4 ±6.05) [4,[7][8][9]27,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the MMSE, the MoCA is a one-page test, which can be administered in five to ten minutes or less. It assesses more cognitive domains than the MMSE, including short-term memory, visuospatial abilities, executive functions, attention, concentration, working memory, language and orientation [3]. Its sensitivity in detecting MCI is 90%, while that of the MMSE is only 18% [4,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the MoCA score is more sensitive to detect the MCI and AD in comparison with MMSE. [59][60][61] In addition, the MoCA has comprehensive coverage of cognitive function, such as executive function attention, attention and delayed recall, while the MMSE lacks these abilities. 62 Recently, Alagiakrishnan et al have compared the usefulness of MoCA with the Standardized MMSE in detecting MCI with T2DM.…”
Section: Discussionmentioning
confidence: 99%